Response of Micronutrients Application to Biomass, Candellila Wax and Biocrude of Euphorbia alltisyphilitica zucco Grown on Gomti Upland Alluvium - Mehrotra, N K; Ansari, S R (Annals of Arid Zone, 2016)
A pot-culture study was made to assess the effects of micronutrients application to soils on growth. biomass and yield of candellila wax and extractive biocrudes of Euphorbia antisyphilitica zucc grown on netural, loamy sand soils of Gomti upland plain. Application of Zn. Cu and Mn besides increasing biomass, increased the plant concentrations of epi-cuticular wax (Alkanes) and acetone extractive resinous hydrocarbons including terpenoids. The best response was in the treatment of Zn + Mn +Cu which increased the biomass by 40% and the concentration of wax and acetone extractives by 232 and 83% respectively. An involvement of micronutrients in the biosynthesis of secondary metabolites of the fuel range, particularly of Cu, Mn and Zn in that order ofr waxes (alkanes) and the acetone extractive resinous hydrocarbons has been indicated. The drY phylloclade tissue nutrient responsive values were found to be 28. 10 and 9 ppm for Zn, Mn and Cu respectively.